2013
DOI: 10.4103/0974-777x.107165
|View full text |Cite
|
Sign up to set email alerts
|

Mortality audit of neonatal sepsis secondary to Acinetobacter

Abstract: Background:Multidrug resistant Acinetobacter infection has emerged as an important pathogen in neonatal sepsis in the recent years causing morbidity as well as mortality.Materials and Methods:A retrospective analysis was performed over a one and a half year period of all neonates admitted with sepsis in our neonatal intensive care unit (NICU), who developed Acinetobacter infection and to identify mortality-associated risk factors in these neonates.Results:Incidence of neonatal septicaemia due to Acinetobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 7 publications
6
25
1
Order By: Relevance
“…Staphylococcus aureus was the predominant isolate may be from carriers as we got some carriers from NICU on MRSA surveillance. The results of the present study were comparable with the study conducted by De A Set al [5] , Sankar MJ et al [8] , Roy I et al [12] and Shah AJ et al [13] . Neonatal sepsis is a serious national health concern.…”
Section: Discussionsupporting
confidence: 82%
“…Staphylococcus aureus was the predominant isolate may be from carriers as we got some carriers from NICU on MRSA surveillance. The results of the present study were comparable with the study conducted by De A Set al [5] , Sankar MJ et al [8] , Roy I et al [12] and Shah AJ et al [13] . Neonatal sepsis is a serious national health concern.…”
Section: Discussionsupporting
confidence: 82%
“…Staphylococcus aureus was the predominant isolate may be from carriers as we got some carriers from NICU on MRSA surveillance. The results of the present study were comparable with the study conducted by De A Set al [5] , Sankar MJ et al [8] , Roy I et al [12] and Shah AJ et al [13] . Neonatal sepsis is a serious national health concern.…”
Section: Discussionsupporting
confidence: 82%
“…[4] On the other hand, multidrug resistant (MDR) strains are emerging. [5] In this perspective, the purpose of the study is to evaluate the results of different diagnostic tests in the presence of risk factors and/or clinical picture. Blood culture, sepsis screen, biochemical markers, cerebrospinal fluid (CSF) study, radiology were included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…A. baumannii infection also occurs in neonatal ICUs. One study reported A. baumannii as the causative agent in 6.2% of cases of septicemia resulting in an overall attributable mortality rate of 20% (7). Higher morbidity and mortality rates have been reported in patients infected with MDR A. baumannii strains as opposed to those infected with non-MDR A. baumannii strains (8).…”
mentioning
confidence: 99%